The determinants of handwashing in humanitarian crisis setting during the COVID-19 pandemic: a multi-country analysis. - Lamb, Jenny; Thorseth, Astrid Hasund; MacDougall, Amy; Thorsen, William; White, Sian (Health Promotion International, 2024)
The Wash'Em process was developed to improve the design of handwashing behaviour change programmes during outbreaks and humanitarian crises. It aims to rapidly create evidence-based, contextualized handwashing programmes. Wash'Em was widely used during the COVID-19 pandemic. This multi-country secondary data analysis compares data emerging from Wash'Em during the pandemic, to understand whether commonalities in programming constraints or the determinants of handwashing behaviour existed across countries. Wash'Em datasets (n  = 38) were verified prior to inclusion in secondary data analysis; descriptively summarized and then statistical summaries of homogeneity were derived. Wash'Em was implemented as intended during the pandemic, typically taking a small number of humanitarian staff less than a week to complete. Most actors reported using the recommendations suggested by the process but did so within relatively short-term and poorly financed prevention programmes. Homogeneity in the responses to the Wash'Em tools was low indicating that the determinants of handwashing behaviour during the pandemic were predominantly shaped by pre-existing factors rather than the nature of the health threat. Hygiene programmes during outbreaks should avoid 'copying and pasting' interventions from one setting to another and instead make time to holistically understand the behavioural determinants in a specific context and develop programme activities that are designed to address these. Particular attention should be given to factors in the physical and social environment that may enable or constrain handwashing behaviour, pre-existing disease vulnerabilities and the secondary and non-health impacts of outbreaks. Wash'Em provides one feasible way of contextualizing handwashing interventions in outbreak or humanitarian settings.